Nickel Allergy in Adults in the US. Issue 5 (September 2015) - Goldenberg, Alina; Vassantachart, Janna; Lin, Elaine J.; Lampel, Heather P.; Jacob, Sharon E.
<x xml:space="preserve">Abstract</x> Abstract Although a significant number of nickel dermatitis cases are seen clinically, most cases are neither patch-tested nor captured in the literature, allowing for a prospering hidden nickel epidemic. We present a qualitative review utilizing the public medical library of peer-reviewed US adult nickel dermatitis cases with the goal of identifying regional variations and trends. Between 1962 and 2015, 18, 251 adult patients were reported to be sensitized to nickel. The number of articles has exponentially increased over the past 5.5 decades as 4.3% of total cases were reported between the 1960s and 1990s, 31.3% between 2000 and 2009, and 64.3% were reported between 2010 and 2015. Geographically, 27 US states have had at least 1 reported case of adult nickel dermatitis. Rising rates of US nickel dermatitis noted in our findings further highlight the need for medical professionals, legislators, and manufacturers to advocate for regulation of nickel-containing items.